PRINSIP KESETIAAN MELAYANI RASUL PAULUS: SEBUAH STUDI EKSEGETIS KISAH PARA RASUL 20:24 - David Susilo Pranoto (Manna Rafflesia, 2015)
The God who calls believers into the noble calling task is a faithful God. In carrying out this call of duty the believer must be faithful like God the creator. The task of that vocation is to serve God and preach the gospel throughout the face of the earth. Loyalty to serve to the end is what God wants for every believer, this must be owned by every servant of God and believers, as the Apostle Paul emphasized in the book "Acts 20" as a servant of the Lord the Apostle Paul completed his vocation properly. In "Revelation 2: 10b" let you be faithful unto death, I will grant you the crown of life. This is God's promise for everyone who is faithful to Him and who completes the call of duty well to the finish line. Through the article is expected to encourage believers to understand eating loyalty.